2006
DOI: 10.1306/st571314
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Petroleum Geology of Deepwater Setting

Abstract: Cover images: from top left clockwise: (a) Outcrop photograph of the thinning-upward sheet sandstones, Lower Pennsylvanian Jackfork Group, Baumgartner Quarry, Arkansas. (b and c) Core photograph and image log are from the Upper Cretaceous Dad Sandstone, Lewis Shale, Wyoming. Images are from the CSM Strat Text #61 core (Chapters 6, 7, 12). (d) Seismic profile across the Marlim Field, Campos Basin (Chapter 15). Figure courtesy of Carlos Bruhn and AAPG. (e) 3-D image of the reservoir interval at the Thunder Horse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 0 publications
3
43
0
3
Order By: Relevance
“…The nature of dark matter is the most prominent one, at a somewhat larger scale, both in terms of actual size and in terms of scientific credibility; there is zero-point energy that imbalance our theoretical manifestation of cosmology [6][7][8]. The solution of this unexplained phenomenon could deepen our understanding of the universe and also provide us tools for more scientific exploration rather than limiting ourselves from the whirlpool of speculation and uncertainties, we'll have something absolute in our hands to mold and engineer gravitational waves.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of dark matter is the most prominent one, at a somewhat larger scale, both in terms of actual size and in terms of scientific credibility; there is zero-point energy that imbalance our theoretical manifestation of cosmology [6][7][8]. The solution of this unexplained phenomenon could deepen our understanding of the universe and also provide us tools for more scientific exploration rather than limiting ourselves from the whirlpool of speculation and uncertainties, we'll have something absolute in our hands to mold and engineer gravitational waves.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Posamentier and Kolla (2003) proposed that deepwater channel sedimentary systems consist of low-sinuosity channel fills, natural levee deposits, distributary channel complex, lobe, sand sheet and splay units. Weimer et al (2007) identified sedimentary units, such as mass transport sedimentary systems, sliders, channel deposits, levee deposits, lobes, sand sheets, thin-bedded deposits and condensation beds. Li et al (2012) divided deepwater gravity flow deposit units on passive continental margins into mass transport sedimentary systems, channel-levee complex and lobes.…”
Section: Introductionmentioning
confidence: 99%
“…Deepwater sedimentary (depositional) system (DSS or DDS) is becoming more and more important for its significance to deepwater hydrocarbon exploration (Wynn et al, 2007;Navarre et al, 2002;Stow and Mayall, 2000). The deepwater depositional systems are those formed under gravity-flow processes and located somewhere from the upper to middle slope regions to the floor of a basin (Weimer and Slatt, 2007).…”
Section: Introductionmentioning
confidence: 99%